2022
DOI: 10.3389/fpsyg.2022.879123
|View full text |Cite
|
Sign up to set email alerts
|

Early Word Segmentation Behind the Mask

Abstract: Infants have been shown to rely both on auditory and visual cues when processing speech. We investigated the impact of COVID-related changes, in particular of face masks, in early word segmentation abilities. Following up on our previous study demonstrating that, by 4 months, infants already segmented targets presented auditorily at utterance-edge position, and, using the same visual familiarization paradigm, 7–9-month-old infants performed an auditory and an audiovisual word segmentation experiment in two con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
(118 reference statements)
0
6
0
1
Order By: Relevance
“…Furthermore, Deoni’s study also showed that SES, birth weight and gestation duration were protective factors, since children with lower SES, lower weight and/or shorter gestation were more affected. In a similar line, Frota et al (2022) found that post-pandemic children exhibited lower performance at word segmentation tasks than pre-pandemic children.…”
Section: Introductionmentioning
confidence: 72%
“…Furthermore, Deoni’s study also showed that SES, birth weight and gestation duration were protective factors, since children with lower SES, lower weight and/or shorter gestation were more affected. In a similar line, Frota et al (2022) found that post-pandemic children exhibited lower performance at word segmentation tasks than pre-pandemic children.…”
Section: Introductionmentioning
confidence: 72%
“…Syllables, in turn, may serve as the framework for phoneme representations [ 31 ]. Unlike Portuguese, where syllable-timing is prevalent, Greek leans towards stress-timing [ 32 ]. Therefore, the question arises: why would entrainment to stress rates enhance speech encoding in Greek participants?…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the prevalence of ASD in 2020 to 2021 markedly increased. As an explanation for the increased prevalence of ASD during the COVID-19 pandemic, we suggest that measures like mask-wearing during the COVID-19 pandemic might have interfered with children's development, especially language development, in which children learn by looking at their caregivers' mouths and facial expressions [29,30]. Due to self-isolation and social distancing to prevent the spread of infection, professional education hours have decreased in daycare centers, and children with ASD symptoms have experienced an aggravation of psychiatric and behavioral problems [31,32].…”
Section: Discussionmentioning
confidence: 99%